INTERNATIONAL LAW & INTERNATIONAL RELATIONS: INTERSECTION - Téllez Núñez, Andrés; Pontificia Universidad Javeriana (Editorial Pontificia Universidad Javeriana y Facultad de Ciencias Jurídicas, 2005)
Is there an intersection between the application of Public International Law with the political conduction of international relations? Should International Law, International Order and International Rules be redefined? How can such an intersection be found? The investigation seeks to extrapolate new definitions and an International Law axiom by utilizing sundry approaches to the state of the question which is properly laid out as well as some terms defined previous to the discussion by utilizing “approaches.” The investigation is carried out by using the Cartesian method or that of Descartes and followers and the formal and material logical structures. Eventually new definitions and an axiom by extrapolating analyses categories are laid out. Hence, approaches such as the “legalistic” one, the “natural law” one, the “religious,” the “extra-legal” one, the “eclectic” one, the “effective” one and the “UN proposed” one are analyzed in-depth upon observing the experience and current factual situation even though noting that those approaches are neither mutually exclusive nor “pure,” but representative as the examples supporting them show. The paper’s bottom line is no other than zeroing in on one of the oldest of International Law’s wounds: That of its effectiveness. But by pointing out various moot points and by reflecting on the different reality stages, one can conclude that the material mission of the law as well as the aims of international order are eventually attained. Nonetheless in concluding and setting out the axioms and new definitions, the existing political power within a democratic framework should not be overlooked as the praxis of International Law meets that of international power to form then a juxtaposition. So, regardless of some international instruments being deemed as substantial law, one has to ask whether what the international community calls “breaking of law,” is rather a breaking of procedures or adjective mandates.